Situation of the indebtedness of the organizations of sports facilities management of non-competitive leisure. An empirical study - Grimaldi-Puyana, M.; Gálvez-Ruiz, P.; Sánchez-Oliver, A. J.; Alcaraz-Rodríguez, V. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The management of the debt in sports organizations are determinant variables for the survival of these, the lack of control can affect the proper functioning of an entity. According to the existing data, the organizations that manage golf courses enjoy a good economic situation. Therefore, the purpose of this study was to know the status and evolution of the debt of sports companies that participate in the sport of non-competitive golf. For this, a sample of 93 organizations throughout the Spanish territory was selected with an average age of 20,08 years. In order to obtain the data, the economic information of the Iberian Balance Sheet Analysis System of the past decade was used. From the findings obtained in the present study, an increase in the average debt of the organizations of 70,5% follows after a decade. In spite of the good economic health and the increase of its income by exploitation and total of assets in the period of study, we can affirm that the debt of these organizations has increased exponentially between 2005-2015.